Numerical Analysis of Different Slit-Check Dams - İkinciogullari, Erdinc; Emıroglu, Muhammet Emin (My University, 2023)
Check dam designs have attracted attention recently due to the clogging of classical check dam structures with sediment and wooden material carried during the flood quickly. These structures regulate flow characteristics and debris flow. However, until now, the impacts of these structures on flow characteristics have received little attention in the literature. Therefore, it is necessary to develop new models to increase these structures' trapping capacity or extend the clogging time. In this study, the flow characteristics of check dams with horizontal, vertical, and angled openings were numerically analyzed for two-phase (water and air) flow. The numerical model was validated using experimental results in the literature. For the study in which twelve analyses were performed, four different check dam models (i.e., check dam with the classical, the narrow horizontal opening, the vertical openings, and angled openings) and three different unit flows (0.04, 0.03, and 0.02 m3 s-1 m-1) were used in the analysis. The open-source software OpenFOAM and the k-? SST turbulence model were used for the numerical analysis using the Computational Fluid Dynamics (CFD) method. The highest energy dissipation rate among slit check dam models was seen in Model-3 at maximum unit flow, whereas it was attained in Model-2 at minimum unit flow. There is no difference in the energy dissipation rate at low unit flows whether the openings are positioned vertically or angled; nevertheless, the vertical model (Model-3) is observed to be more efficient at maximum unit flow.
Keywords: CFD; OpenFOAM; Slit check dam; horizontal openings; vertical openings; angled openings